Prevalence of Cardiac Diseases in Cats - Vishnu Vardhan, Mypati; Basava Reddy, Kype; Shobhamani, Bollam; Vijaya Lakshmi, Siddavatam (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study was aimed to determine the prevalence of cardiac diseases in cats presented to the Super-Speciality Veterinary Hospital,  SVVU, Visakhapatnam, based on breed, age, gender and body weight. Of the 2,872 cats presented from April 2024 to March 2025, 164  cats with symptoms of cardiac disease were subjected to physical examination, electrocardiography, echocardiography and haemato biochemical analysis. Hypertrophic cardiomyopathy (HCM) was diagnosed based on an end-diastolic interventricular septum or left  ventricular posterior wall thickness ≥6 mm on M-mode, while restrictive cardiomyopathy (RCM) was confirmed by normal wall thickness,  an LA/Ao ratio >1.5 on M-mode, and an E/A ratio >2 on pulsed-wave Doppler echocardiography. Among them, 10 were diagnosed with  HCM and 6 with RCM. The overall prevalence of cardiac diseases in the total presented cases was 0.56 %, while among the 164 screened  cases, 9.76 % had cardiomyopathy. The HCM accounted for 6.10 % and RCM for 3.66 %. HCM was more prevalent in Persian cats (80%),  whereas RCM was more common in non-descript cats (66.6%). Cardiomyopathy was most commonly observed in cats aged 5-10 years  (75%), with a higher prevalence in males (68.7%) and those weighing 3 to 5 kg (81.25%). The study concluded that HCM is the most  prevalent cardiomyopathy in Persian cats.
Keywords: Cat; Hypertrophic cardiomyopathy; Pulsed-wave Doppler echocardiography; Restrictive cardiomyopathy; Risk factors